2019
DOI: 10.1530/joe-18-0432
|View full text |Cite
|
Sign up to set email alerts
|

Vincamine as a GPR40 agonist improves glucose homeostasis in type 2 diabetic mice

Abstract: Vincamine, a monoterpenoid indole alkaloid extracted from the Madagascar periwinkle, is clinically used for the treatment of cardio-cerebrovascular diseases, while also treated as a dietary supplement with nootropic function. Given the neuronal protection of vincamine and the potency of β-cell amelioration in treating type 2 diabetes mellitus (T2DM), we investigated the potential of vincamine in protecting β-cells and ameliorating glucose homeostasis in vitro and in vivo. Interestingly, we found that vincamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…As previously mentioned, VIN is a compound with multiple mechanism of actions. Several studies have shown that it is a PDE1 inhibitor, a GPR40 agonist, and a blocker of VGNC (Abdel-Salam et al, 2016; Du et al, 2019; Sheref et al, 2021). The effect of PDE inhibitors has been widely studied in several PD models.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously mentioned, VIN is a compound with multiple mechanism of actions. Several studies have shown that it is a PDE1 inhibitor, a GPR40 agonist, and a blocker of VGNC (Abdel-Salam et al, 2016; Du et al, 2019; Sheref et al, 2021). The effect of PDE inhibitors has been widely studied in several PD models.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have indicated the potential role of nutraceuticals, such as VIN as well as its semi-synthetic derivative vinpocetine, to target the underlying neurodegenerative processes of PD (Lama et al, 2020).VIN exhibits antioxidant and anti-inflammatory activities, and may work through several mechanisms of action. It is a phosphodiesterase (PDE) I inhibitor, a blocker of voltage-gated Na + channels (VGNC), and a GPR40 agonist (Abdel-Salam et al, 2016;Du et al, 2019;Sheref et al, 2021). VIN is commercially available in the United States as a health care product with nootropic function, and exerts a beneficial effect in a number of brain disorders of elderly patients, such as memory disturbances, vertigo, transient ischemic deficits and headache (Fandy et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This may have been caused by a decrease in glucotoxicity via the glucose-lowering activity of SCO-267. Furthermore, it has been reported that vincamine, a monoterpenoid indole alkaloid, which activates GPR40, protected STZ-treated INS-832/13 cells, a rat insulinoma cell line, through GPR40 activation (Du et al, 2019), and CNX-011-67, a GPR40 agonist, reduces inflammation-induced apoptosis of NIT1 cells, a mouse pancreatic β-cell line (Verma et al, 2014). Overall, SCO-267 may improve β-cell function via a direct GPR40-mediated effect.…”
Section: Discussionmentioning
confidence: 96%
“…NOTCH1 regulated the PI3K/Akt pathway through targeting FOXC2, thus regulating glucose and lipids metabolism in type 2 diabetes model cells A previous study showed that FOXC2 could regulate the PI3K/ Akt pathway in colorectal cancer 24 . The PI3K/Akt pathway was reported to play an important role in regulating glucose metabolism 25 . Here, we aimed to explore regulating relationships between NOTCH1, FOXC2 and the PI3K/Akt pathway in regulating glucose and lipids metabolism, so we both overexpressed NOTCH1 and knockdown FOXC2 in HG-treated HepG2 cells.…”
Section: Mir-363 Regulated Glucose and Lipids Metabolism In Type 2 Di...mentioning
confidence: 99%